SOCIAL PROOF AND URGENCY CAN MEDIATE THE INFLUENCE OF TIKTOK ADS ON PURCHASING DECISIONSOF BANK SYARIAH INDONESIA IN THE MAKASSAR AREA 2021-2025 - Arif Riyanto; Muhamad Risal Tawil; Adhitya Chandra Setyawan; Bagus Ananda Kurniawan; Petrus Valentino Baunsele (ITB AAS Indonesia Surakarta, 2026)
The rapid evolution of digital marketing has transformed how financial institutions engage with potential customers, particularly within the Islamic banking sector. This study aims to analyze the mediating role of Social Proof and Urgency in the relationship between TikTok Ads and Purchasing Decisions of Bank Syariah Indonesia (BSI) products among customers in the Makassar area between 2021 and 2024. As the largest Sharia bank in Indonesia, BSI faces the challenge of maintaining relevance among a younger, digitally native demographic. Using a quantitative research design, this study examines how the visual and algorithmic nature of TikTok advertisements triggers psychological mechanisms—specifically social validation and the fear of missing out (urgency)—to accelerate the decision-making process. Data were gathered through structured questionnaires distributed to 400 respondents in Makassar, selected using purposive sampling. The results indicate that TikTok Ads have a positive and significant direct influence on purchasing decisions. Furthermore, Social Proof and Urgency act as partial mediators, significantly strengthening the impact of digital advertising on customer acquisition. These findings suggest that for Islamic banks, the combination of creative content on TikTok and psychological triggers can overcome the traditional barriers of complex banking products. This study provides strategic implications for BSI to optimize its digital marketing budget by focusing on community-driven content and time-sensitive offers to foster trust and immediate action in a competitive market. Keywords: TikTok Ads, Social Proof, Urgency, Purchasing Decisions, Bank Syariah Indonesia, Sharia Marketing.